2022
DOI: 10.1097/aln.0000000000004443
|View full text |Cite
|
Sign up to set email alerts
|

Nonopioid Analgesic Prescriptions Filled after Surgery among Older Adults in Ontario, Canada: A Population-based Cohort Study

Abstract: Background The objective was to assess changes over time in prescriptions filled for non-opioid analgesics for older post-operative patients in the immediate post-discharge period. We hypothesized that the number of patients who filled a non-opioid analgesic prescription increased over the study period. Methods We performed a population-based cohort study, using linked health administrative data, of 278,366 admissions ≥66 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…A study utilizing large nationwide data in the United States found that the average predicted probability of patients undergoing major surgery being prescribed two or more non-opioid analgesics was 54.2%, with tremendous variation in non-opioid analgesic prescriptions among hospitals [ 21 ]. A recent study in Ontario, Canada, targeting elderly patients aged 66 and over, found that 21% of all patients were prescribed only opioids within one week after surgery [ 22 ]. Although the prescription of non-opioid analgesics showed an increasing trend during the study period, the number of patients receiving a combination of two or more non-opioid analgesics remained low [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study utilizing large nationwide data in the United States found that the average predicted probability of patients undergoing major surgery being prescribed two or more non-opioid analgesics was 54.2%, with tremendous variation in non-opioid analgesic prescriptions among hospitals [ 21 ]. A recent study in Ontario, Canada, targeting elderly patients aged 66 and over, found that 21% of all patients were prescribed only opioids within one week after surgery [ 22 ]. Although the prescription of non-opioid analgesics showed an increasing trend during the study period, the number of patients receiving a combination of two or more non-opioid analgesics remained low [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in Ontario, Canada, targeting elderly patients aged 66 and over, found that 21% of all patients were prescribed only opioids within one week after surgery [ 22 ]. Although the prescription of non-opioid analgesics showed an increasing trend during the study period, the number of patients receiving a combination of two or more non-opioid analgesics remained low [ 22 ]. In addition, according to a survey on perioperative management in thoracic surgery in the UK and Ireland, postoperative use of acetaminophen was reported in 98% of cases, while the use of NSAIDs was only 55% [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…3 NSAIDs are available in prescription and over-the-counter (OTC) strengths, a variety of different formulations, and oral (most common), intravenous, injectable and topical forms. The use of NSAIDs has risen globally throughout the last 20 years, [4][5][6][7][8] in part due to increasing rates of chronic and persistent pain and an increasing ageing population.…”
Section: Introductionmentioning
confidence: 99%
“…3 NSAIDs are available in prescription and over-the-counter (OTC) strengths, a variety of different formulations, and oral (most common), intravenous, injectable, and topical forms. The use of NSAIDs has risen globally throughout the last twenty years, [4][5][6][7][8] in part due to increasing rates of chronic and persistent pain and an increasing aging population.…”
Section: Introductionmentioning
confidence: 99%